POPULASI Bemisia tabaci (GENNADIUS) PADA PERTANAMAN CABAI DI YOGYAKARTA: STUDI KASUS PADA DAERAH ENDEMIK DAN NON ENDEMIK PENYAKIT KERITING KUNING CABAI - Ahmad Taufiq Arminudin; Arman Wijonarko; Y. Andi Trisyono (Jurnal Agroteknologi, 2010)
This research was aimed to study actual population of Bemisia tabaci, the vector of Pepper Yellow Leaf Curl Virus, in endemic and non endemic areas of Pepper Yellow Leaf Curl Disease (PYLCD) at Yogyakarta through population of its adult and immature. Field observation was taken at Sleman District as endemic areas and Bantul district as non endemic areas. We took sticky yellow trap and modified vacuum to collect actual population of adult whiteflies, whereas the immature were observed by direct counting and collecting the infested leaf of chili. The next activity was identifying and analyzing male and female the population by binocular microscope at Entomology Laboratory Faculty of Agriculture Gadjah Mada University Yogyakarta. The results showed that adult population of B. tabaci in endemic areas was higher than non endemic areas of PYLCD on chili vegetative phase, whereas the immature population was lower. This condition indicated that migration pattern has been occurred on population B. tabaci.